Stress — Differential induced divergence with application to littoral precipitation - Bryson, Reid A.; Kuhn, Peter M. (ERDKUNDE, 1961)
The work points out the connection which exists between the land-sea stress differential, the divergence caused thereby at the coast and sinking air, and the dryness of such coasts where the land is on the low pressure side of the wind. This connection, however, would seem to be a purely accidental one, unless it could also be shown that these dry coasts are more than just the lines along which the land-sea boundary crosses a large desert zone caused by an extensive sinking air movement in connection with the planetary wind system. This question was broached by Lydolph (11), who found in his investigation discussed in this report that they are indeed drier than their hinterlands. This indicates that a local factor of the coastal zone itself must be taken into account. He also points to an example showing that convergence in an area , where the land is on the high pressure side of the wind, coincides with coastal moisture. It will be obvious to a climatologist that numerous other areas fit into this general scheme. For example, in the case of the Pacific coast of America, the boundary between the wet and dry coasts is likewise nearly the dividing line between the land area situated to the right and the land area situated to the left of the wind. A brief consideration also shows that the same wind that drives the surface water away from the coast must also cause upwelling of the deep water. Conversely, convergence of the air must also coincide with convergence of the water toward the coast. From this it follows that the classical factor of rising cold water to explain dry coasts comes from the same cause as the sinking air movement. This common cause is the relative orientation of the coastline to the direction of air flow. Although the present discussion focuses on this climatic phenomenon on coasts, there is no reason why similar contrasts of surface relief on the mainland should not produce similar divergences. Although it is not possible to apply this principle quantitatively for lack of necessary records of the relationship between braking factor and surface form, the qualitative implications are evident. For example, a southerly wind over the lower Mississippi Valley would have to be convergent on the steep slopes along the eastern valley flank and divergent over the western valley flank. This, in turn, would have to characterize the eastern valley slopes as a location favored for thunderstorm formation. It is the task of further research to answer this question.